Kryptochroma: a new genus of bark-dwelling crab spiders (Araneae, Thomisidae) - Machado, Miguel (2021)
A recent phylogenetic analysis has shown that the genus Stephanopis comprises several different lineages of bark-dweller crab spiders. The ones with South American distribution that presenta close relationship with other Neotropical genera like Epicadus, Onocolus, Rejanellus and Epicadinus were recovered in a single clade, with good support and stability. Here, we present a taxonomic review of Stephanopis species attributed to the ?pentacantha clade?, proposing the new genus KryptochromaMachado gen. nov. to accommodate them. New distribution records are provided and the following species are described for the first time: Kryptochroma gigas Machado & Viecelli gen. et sp. nov., Kryptochromahilaris Machado & Teixeira gen. et sp. nov., Kryptochroma quadrata Machado & Viecelli sp. nov. and Kryptochroma septata Machado & Teixeira sp. nov. The species Stephanopis borgmeyeri is considered a nomen dubium, Stephanopis aheneus is a junior synonym of Epicadus tuberculatus, Stephanopisquimiliensis is transferred to Ulocymus and Stephanopis stelloides is transferred to Epicadus, being Epicadus stelloides the senior synonym of Stephanopis salobrensis, Stephanopis trilobata and Epicadus caudatus.